MENULIS UNTUK PUBLIKASI: “PUNYA IDE, TAPI SULIT MENULISKANNYA” - Wienanda, Wahyu Kartika; Harnita Sari, Yohana Ika; Liani, Triana April; Utami, Azalea Puteri (Jurnal Vokasi Indonesia, 2021)
Writing for publication is the scholars’ needs. Unfortunately, the number of student publications, especially in the Applied English Study Program, Sekolah Vokasi UGM, has not shown a good trend. Thus, the study program provides a subject namely Academic Writing to help the students practice and improve their research writing skills. However, specifically-tailored course materials for the subject have not been provided. This study aims to find out the students’ needs for writing a research publication. Interviews to 20 students of Transfer Program in Applied English and 3 journal reviewers were conducted. The interview results were then analyzed based on parts of research articles, namely IMRaD (Introduction, Methods, Results, and Discussion) to understand the important aspects to be included in each part. The findings show that students need academic writing skills in every aspect of research writing: 1) in Introduction, the research gap is essential; 2) in Methods, explaining research methods should be done rigorously; 3) in Findings/Results, effective and elaborated findings are important; 4) in Discussion, the discussion beyond confirmation and contrasting findings is needed; and 5) in Conclusion, the research implication(s) is pivotal. These are in line with statements of journal editors mentioning about the characteristics of each part of the research manuscript and the important points to be included in them. This study, therefore, can be used as reference to tailor course materials for Academic Writing course.